2017
DOI: 10.1073/pnas.1706085114
|View full text |Cite
|
Sign up to set email alerts
|

Ideals, practices, and future prospects of stakeholder involvement in sustainability science

Abstract: SignificanceEven though stakeholder involvement (SI) is increasingly relevant in scientific research processes, especially in interdisciplinary fields like sustainability science, there is limited academic literature investigating conceptual or methodological questions. Through a survey among researchers from this field, this paper presents an overview of practices and ideals of SI as well as of their divergence. Furthermore, trade-offs between scientific ideals and SI, as well as necessary improvements concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…On the one hand, it would be desirable to organize this at the global level, as most of the relevant mean sea level studies are global in scope. On the other hand, whether expert judgment is perceived to be authoritative by decision makers is often determined by national authority, and face‐to‐face interactions and the development of mutual trust between experts and users (Brandt et al, ; Mielke et al, ; Reed, ). For example, the current provisioning of SLR scenarios is generally organized nationally or even more locally in the case of big cities such as London, New York, and Tokyo, which have the resources and expertise to run their own expert processes (Le Cozannet, Nicholls, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, it would be desirable to organize this at the global level, as most of the relevant mean sea level studies are global in scope. On the other hand, whether expert judgment is perceived to be authoritative by decision makers is often determined by national authority, and face‐to‐face interactions and the development of mutual trust between experts and users (Brandt et al, ; Mielke et al, ; Reed, ). For example, the current provisioning of SLR scenarios is generally organized nationally or even more locally in the case of big cities such as London, New York, and Tokyo, which have the resources and expertise to run their own expert processes (Le Cozannet, Nicholls, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies focusing on stakeholder inclusion in health research, have often been from the perspective of the researchers. Factors such as the difficulty of finding stakeholders with the right skills and knowledge who are interested and available to participate or the difficulty of dedicating time to stakeholder engagement in a context where it isn’t measured and may not be valued [39, 40], have been the focus rather than the perspective of the stakeholders and their motivations for becoming involved. The case studies reported here provide insight into the motivations from the stakeholder perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Since the data was collected from industry-expert stakeholders, the author acknowledges the challenges that go along with such an approach, ranging from the kind of knowledge produced in such stakeholder interactions to the science-policy-interface that is perceived and used differently by stakeholders and scientists. For a discussion of challenges of stakeholder involvement in science, see Mielke et al (2016Mielke et al ( , 2017 and for a specific discussion on close dialogue with industry stakeholders, see Clark (1998).…”
Section: Critical Reflection Of the Methodsmentioning
confidence: 99%